Gasdermin D: A potential mediator and prognostic marker of bladder cancer - El-Gamal, Randa; Abdelrahim, Mona; El-Sherbiny, Mohamed; Enan, Eman T.; El-Nablaway, Mohammad (Frontiers in Molecular Biosciences, 2022)
Background: Bladder cancer is considered one of the commonest widespread cancers, its presentation ranges from non-muscle invasive form to being muscle-invasive. The gasdermin family of proteins consists of six proteins. Members of gasdermin family are involved in pyroptosis; which is considered as type of inflammatory apoptosis via participation of GSDMD and inflammatory caspases. Purpose: The goal of this research was to look into the potential involvement of gasdermin D in pathogenesis of bladder cancer, In addition, to investigate its potential role as a prognostic marker of bladder cancer. Methods: Gasdermin D gene and protein expression was examined in fresh frozen 80 bladder cancer specimens (30 NMIBC, and 50 MIBC) and the matching 80 control tissue samples utilizing real-time polymerase chain reaction and western blotting. Furthermore, the immunoreactivity of gasdermin D protein was also detected by immunohistochemistry. • Results: Gasdermin D gene and protein expression showed a highly significant difference between the control and the two bladder cancer groups (p <0.001), as demonstrated by real-time PCR, western blotting and immunohistochemistry. Cox proportional hazards regression models showed that lower gasdermin D gene expression in cancer patients (≤1.58-fold), and younger age (≤53 years) were linked with a higher risk of local tumor recurrence. Moreover, higher gasdermin D gene expression (>2.18-fold), and lymph nodes’ involvement were associated with an increased mortality. Conclusions: Gasdermin D is involved in the pathogenesis of bladder cancer and muscle invasion, in addition, tissue gasdermin D expression may be used as useful tool to predict local tumor recurrence.